Predictive Effect of Grit Personality on Academic Engagement Among Undergraduate Physical Education Students: The Mediating Role of Resilience - Juan José Calleja-Núñez; Raúl Baños; Roberto Espinoza-Gutiérrez; Antonio Granero-Gallegos (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The primary objective of this study was to examine the mediating effect of resilience in the relationship between GRIT personality and academic engagement among undergraduate students majoring in physical education. A study was conducted using a non-experimental, cross-sectional, correlational-cause design. The study included a total of 1164 Mexican students, with an average age of 21.21 years (standard deviation = 3.26). The sample consisted of 30.0% female participants, 69.6% male participants, and 0.4% participants who identified as others. The researchers utilised the GRIT personality, resilience, and academic engagement scales in their study and performed a structural equation analysis incorporating latent variables. The findings derived from the structural equation model indicate a positive association between perseverance of effort and both behavioural and emotional academic engagement, while also revealing a negative correlation between perseverance of effort and behavioural disaffection. Moreover, the presence of resilience in students is associated with a notable increase in their behavioural and emotional involvement, while concurrently leading to a decrease in emotional disengagement. The phenomenon of interest consistency has been found to have predictive value for both emotional and behavioural disaffection.